Fungi from Hair Wigs as Potential Public Health Concern among Female Students - Iqbal, Muhammad Naeem; Ashraf, Asfa (International Journal of Molecular Microbiology, 2025)
Fungal contamination in hair wigs is an underappreciated public health hazard for female students, with risks ranging from minor scalp irritation to serious infections. Wigs can act as fomites, promoting the spread of fungal pathogens. Synthetic wigs, while less prone to fungal development, can nevertheless retain moisture and heat, providing a breeding environment for fungus if not cleaned on a regular basis. The combination of contagious pathogens, shared living environments, and low awareness heightens these risks for students. In this issue, Yuana et al. (2025), report the fungal species such as Aspergillus niger, A. fumigatus and A. ocharaceus to be contaminant of human Hair wig of female students. The burden of wig-related fungal infections can be mitigated by emphasising education, sanitation, and access to quality wigs and healthcare.